Prevalence and factors associated with neonatal sepsis in Mali: a cross-sectional study - Bienvenu Salim Camara; Alexandre Delamou; Haoua Dembele; Hamadoun Sangho; Birama Apho Ly; Sidikiba Sidibé; Alioune Camara; Cheick Sidya Sidibé; Alhassane Diallo; Abdoulaye Touré; Fatoumata Bintou Traoré; Elhadj Marouf Diallo; et al. (BMJ Open)
Objective This study aimed to assess the prevalence and risk factors for neonatal sepsis among neonates admitted to selected health facilities in the Bamako district and Koulikoro region in Mali.Design This is a prospective cross-sectional study. Data were analyses using bivariate and multivariate logistic regression.Setting This facility-based study was conducted in four health facilities consisting of two hospitals and two reference health centres in Mali.Participants The study participants comprised 795 randomly selected neonates and their indexed mother.Outcome measures The primary outcome of the study was the prevalence of sepsis in the considered health facilities. The other variables of interest were risk factors for sepsis.Results The prevalence of neonatal sepsis among the study population was 21.00%. More than 74% of sepsis cases were early onset (<72 hours). Neonatal age <7 days (AOR=2.79, 95% CI 1.59 to 4.89, p=0.000), low birth weight <2500 g (AOR=2.88, 95% CI 1.41 to 5.86, p=0.003), Apgar score <7 (AOR=4.03, 95% CI 3.09 to 5.24, p=0.000), mother with no education (AOR=2.24, 95% CI 1.15 to 4.33, p=0.02), maternal fever (AOR=2.31, 95% CI 1.53 to 3.53, p=0.000), prolonged rupture of membranes (AOR=1.87, 95% CI 1.01 to 3.54, p=0.04) and prolonged labour (AOR=2, 95% CI 1.03 to 3.88, p=0.04) were significantly associated with neonatal sepsis.Conclusion The prevalence of sepsis in Mali is still high. Given the country’s current security context, the findings in this study can support prevention activities, particularly given the limited resources available. It is essential to facilitate antenatal and postnatal visits, to promote in-facility births and rigorous monitoring of neonates at high risk of sepsis. Furthermore, it would be beneficial for future research on neonatal sepsis to include neonates born at home.